(untitled) (CIPEEX, 2025)
Mycobacterium tuberculosis (Mtb) is a respiratory pathogen, with bacilli transmitted through the inhalation of droplets from contagious individuals via coughing, speaking, singing, and sneezing. Although the disease is preventable and curable, it primarily affects the lungs, leading to respiratory failure and, ultimately, death. It is believed that the disease originated from environmental mycobacteria that entered human populations in the Horn of Africa over 70,000 years ago. Evolving with humans over millennia, Mtb is highly adapted to the human immune system. In 1993, the World Health Organization (WHO) recognized tuberculosis as a global epidemic. As a result, the fight against tuberculosis became one of the eight Millennium Development Goals (MDGs) of the United Nations. Despite significant progress, the COVID-19 pandemic has further complicated the fight against tuberculosis. During the pandemic, there was a decrease in the number of people diagnosed with tuberculosis, an increase in the number of deaths, and a decrease in the number of people treated, highlighting that the pandemic has exacerbated the situation, leaving us in a state of global regression. This study aims to correlate the COVID-19 pandemic with the increase in tuberculosis cases in Brazil between 2020 and 2023. This epidemiological study analyzes the increase in tuberculosis cases in Brazil through consultation with DATASUS. Data were collected from PubMed and Scielo. Inclusion criteria were articles in English published between 2020 and 2024, with restricted-access texts excluded. Data analysis involved examining trends in tuberculosis case numbers and assessing the impact of the COVID-19 pandemic. Brazil experienced an increase in tuberculosis cases from 2020 to 2023, with the most significant increase occurring between 2021 and 2022 (approximately 13%). The highest number of cases recorded before the pandemic was 96,083 in 2019. This record was surpassed in 2022 with about 104,000 cases and again in 2023 with approximately 109,000 cases. The WHO reports that the COVID-19 pandemic has reversed years of progress in tuberculosis control, with a reduction in funding for essential services and a reallocation of resources to address COVID-19. Additionally, lockdowns made it more difficult to seek healthcare. Tuberculosis remains the second deadliest infectious disease in the world (after COVID-19), representing a significant global threat. The increase in cases is partly due to the impact of the COVID-19 pandemic on health systems and disease management. It is crucial for the global community to intensify efforts to combat tuberculosis through improved early diagnosis, effective treatments, and prevention programs. Increasing investment in research, education, and public health policies is essential to combat drug resistance and support vulnerable communities.